Viscous flow activation energy adaptation by isothermal spark plasma sintering applied with different current mode. (May 2018) - Xie, Siyao; Li, Ruidi; Yuan, Tiechui; Zhang, Mei; Wang, Minbo; Wu, Hong; Zeng, Fanhao
Abstract: Theoretical understanding in the innate function of electric current on the spark plasma sintering of amorphous powder is very limited. We proposed an improved isothermal model considering particle size evolution in this work to study the effect of current mode on shrinkage of amorphous Fe41 Co7 Cr15 Mo14 Y2 C15 B6 powder. It revealed a reduction in the activation energy from 71.1 ± 1.6 kJ·mol −1 under direct current to 55 ± 2.0 kJ·mol −1 under pulse current, representing a resultant acceleration of densification by adjusting current mode. The enhancement of consolidation is attributed to increase of electric density induced by pulse current. Graphical abstract: Unlabelled Image